Failure mechanism on Ti-6Al-4V material processed using Selective Laser Melting (SLM) - Mubarok, Sukri; Puspitasari, Poppy; Andoko, Andoko; Lubis, Abdul Munir Hidayat Syah; Permanasari, Avita Ayu; Abdullah, Muhammad Ilman Hakimi Chua (2023)
Titanium alloy has been massively used in automotive and aerospace fields, such as Ti-6Al-4V titanium alloy. Further, the emergence of metallic additive manufacturing (AM) technology has been a breakthrough in the workpiece formation, such as selective laser melting (SLM). Besides, additive manufacturing is capable of producing complex metal components with high